Analysis of Firm Value with Dividend Policy as a Moderating Variable: Empirical Evidence on Real Estate Companies on the Indonesia Stock Exchange - Putri, Zeinytha Saskia; Ichsanuddin Nur, Dhani (Universitas Islam Lamongan, 2023)
Firm Value is a form of corporate achievement that is seen from the perspective of some parties such as investors who associate the value of a company from its stock price. This study aims to examine and analyze the effect of liquidity on firm value, profitability on firm value, Dividend policy moderates the effect of liquidity on firm value and Dividend policy moderates the effect of profitability on the value of real estate companies listed on the Indonesia Stock Exchange. The population used in this study is the financial statements of real estate companies listed on the Indonesia Stock Exchange, totaling 61 companies. Sampling used a purposive sampling technique so that a sample of 11 companies was obtained. Analysis of the data used in this study is using descriptive statistics and moderation regression analysis with data processing through SPSS software. The results of the study show that Liquidity (CR) can make a positive contribution to the company value (PBV) of real estate listed on the Indonesia Stock Exchange. Profitability (ROA) can make a positive contribution to the company value (PBV) of real estate listed on the Indonesia Stock Exchange. The dividend policy (DPR) is able to moderate the liquidity (CR) of the company value (PBV) of real estate listed on the Indonesia Stock Exchange. The dividend policy (DPR) is able to moderate the profitability (ROA) of the company value (PBV) of real estate listed on the Indonesia Stock Exchange.